Quantum dot with high ultraviolet absorption as well as preparation method and application thereof
By performing ZnX solution repair and encapsulation treatment on the quantum dot nucleus, quantum dot nucleus-ZnX repair layer-quantum dot shell structure is formed, which solves the problem of limited ultraviolet absorption range of quantum dots in the prior art and achieves efficient ultraviolet absorption Improved capability and stability.
Patent Information
- Application Number
- CN202411560111.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The quantum dots produced in the prior art have limited ultraviolet absorption ranges, which are difficult to meet the need to improve ultraviolet absorption capacity.
By repairing the quantum dot nucleus in ZnX solution and using the precursor solution to encapsulate the repaired quantum dot nucleus to form a quantum dot nucleus-ZnX repair layer-quantum dot nucleus structure, thereby broadening the range of ultraviolet absorption.
It significantly broadens the ultraviolet absorption range of quantum dots, improves the ability of ultraviolet absorption, and improves the efficiency and stability of quantum dots.
Smart Images

Figure CN119463849A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of quantum dot preparation, and in particular, relates to a quantum dot with high ultraviolet absorption, a preparation method and application thereof. Background Art
[0002] Quantum dots are semiconductor nanocrystals with a size of several nanometers, which have obvious quantum size effects and unique optical properties. When stimulated by light or electricity, quantum dots will emit light of a certain wavelength, which is determined by the composition material, size and shape of the quantum dots. Compared with organic materials, quantum dots can provide excellent color purity and thermal stability. These characteristics make quantum dots have potential application value in the fields of lighting, display, solar energy and bio-markers, and have attracted widespread attention.
[0003] At present, the synthesis of efficient and stable quantum dots is mostly achieved by coating the surface of the luminescent core with an organic or inorganic layer, such as CdSe / ZnS core-shell structure quantum dots. In order to be able to be well applied, it is necessary to improve the stability of quantum dots as much as possible, which requires increasing the thickness of the shell layer. However, due to the mismatch of the lattice parameters between the core and the shell, as the number of shells increases, the surface defects also increase, and the luminescence efficiency gradually decreases. Multiple shell coatings, such as CdSe / CdS / ZnS, CdSe / CdSe / ZnS, CdSe / CdS / CdZnS, etc.
[0004] The Chinese patent application number 201610027909.5 discloses a method for preparing CdSe / CdS / ZnS quantum dots, which is characterized by comprising the following steps: ① preparing a Cd precursor by dissolving 5 mmol of 99.9% pure CdO in a mixture of 25 mmol of 99% pure LA and 8 mmol of 95% pure HDA in argon at a certain temperature; ② preparing a Se precursor by dissolving 5 mmol of Se powder in 6.5 mmol of 90% pure TOP; ③ injecting the product obtained in step ② into step 3. In the product obtained in step ①, CdSe nanocrystals are formed, and the temperature is reduced to below 280°C, and the obtained product is washed with hot methanol; ④ Cd(CH2COO)2 and Na2S(9H2O) are alternately injected into the CdSe nanocrystals, and the mixture is kept refluxed at a temperature not higher than 40°C to prepare CdSe / CdS nanocrystals; ⑤ Zn(CH2COO)2 and Na2S(9H2O) are alternately injected into the product obtained in step ④, and the mixture is kept refluxed at a temperature not higher than 40°C to prepare CdSe / CdS / ZnS quantum dots. It increases the efficiency and stability of quantum dots to a certain extent, but there is still room for improvement in efficiency and stability, and the synthesis steps are numerous and complicated, which is not conducive to large-scale production and has great restrictions on the application of quantum dots.
[0005] CN107090291A discloses a method for preparing CdSe / CdZnSeS / ZnS core-shell quantum dots with simple synthesis method, short synthesis time, high quantum efficiency and high stability, characterized by comprising the following steps: (1) mixing and stirring a zinc source, a cadmium source, an organic solvent and an organic ligand, and then heating to 260-320°C, and introducing a protective gas during the entire reaction process; (2) rapidly injecting a uniformly mixed selenium precursor and a sulfur precursor under stirring; (3) starting the timing after the precursor in step (2) is completely injected, and injecting the sulfur precursor again within 0-30s; (4) reacting at 260-300°C for 1-60min. The beneficial effects of the present invention are as follows: CdZnSeS is used as a medium to connect the core CdSe and the shell CdS, the lattice matching between the core and the shell of the quantum dot is high, the photostability and thermal stability are very high, and the quantum yield can reach more than 80%. The present invention has simple synthesis steps, easy operation, and is conducive to large-scale production.
[0006] However, it was found during use that the quantum dots prepared by the above method have a limited ultraviolet absorption range, and it is necessary to broaden the ultraviolet absorption range and improve the ultraviolet absorption capacity. Summary of the invention
[0007] The purpose of the present invention is to provide a quantum dot with high ultraviolet absorption, a preparation method and application thereof. The method of the present invention is used to prepare quantum dots, which broadens the range of ultraviolet absorption, improves the ability of ultraviolet absorption, and improves the efficiency of quantum dots.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing quantum dots with high ultraviolet absorption, wherein the preparation method comprises the following steps:
[0010] 1) preparing the precursor solution required for the reaction;
[0011] 2) preparing quantum dot cores;
[0012] 3) Repairing the quantum dot core using ZnX solution;
[0013] 4) Encapsulating the repaired quantum dot core with a precursor solution to form quantum dots having a quantum dot core-ZnX repair layer-quantum dot shell structure, thereby obtaining the quantum dots with high ultraviolet absorption.
[0014] In the present invention, the quantum dot core composition is one of ZnSe, CdS, ZnS, CdZnS, CdZnSe, ZnSeS or CdZnSeS;
[0015] In the present invention, the ZnX is ZnF2, ZnCl2, ZnBr2, ZnI2, Zn(SH)2, Zn(CN)2 or C 32 H 16 One of N8Zn;
[0016] In the present invention, the quantum dot shell composition is any one or a combination of two or more of ZnS, ZnSe, CdZnSe, CdZnS, ZnSeS or CdZnSeS.
[0017] The present invention utilizes ZnX (X is carboxyl, thiol, halogen, etc.) to repair the quantum dot core. This X-type ligand (such as X is carboxyl, thiol, halogen, etc.) has a strong bond and force with the surface of the quantum dot core body due to the strong affinity of the group. Through the treatment of the quantum dot core by the X-type ligand, the band gap structure of the quantum dot can be changed, and the donor impurity energy level is generated in the quantum dot band gap. The change of the electronic structure causes the reduction of the band gap, and at the same time, a new energy level is generated in the band gap, providing an intermediate band for electronic transition, so that the electrons on the valence band can be excited by a smaller energy to transition to the intermediate state, and then transition from the intermediate state to the conduction band, expanding the delocalization range of the quantum dot photoexciton, thereby broadening the range of ultraviolet absorption and improving the ability of ultraviolet absorption. On the other hand, halogen or thiol can also be used as an intermediate ligand to passivate the cationic defects on the surface of the quantum dot core, thereby improving the efficiency and stability of the quantum dot.
[0018] Furthermore, in step 1), the anion precursor solution is prepared by adding an anion source to an organic solvent or a long-chain alkyl phosphine under an argon environment until the solid is completely dissolved to obtain an anion precursor solution;
[0019] The preparation method of the cationic precursor solution is as follows: in an argon environment, a cationic source is mixed with an organic solvent until the solid is completely dissolved to obtain a cationic precursor solution.
[0020] Furthermore, the anion precursor in step 1) is one or a combination of sulfur precursors and selenium precursors; the cationic precursor is one or a combination of zinc precursors and cadmium precursors.
[0021] Furthermore, the molar concentration of the sulfur precursor solution is 0.2-2 mmol / ml, and the synthesis method is: under an argon environment, a sulfur source is added to an organic solvent or a long-chain alkyl phosphine, and the sulfur precursor solution is obtained by heating and keeping the temperature.
[0022] Furthermore, the molar concentration of the selenium precursor solution is 0.1-2mmol / ml, and the synthesis method is: under an argon environment, a selenium source is added to an organic solvent or a long-chain alkyl phosphine, and heated and kept warm until the solid is completely dissolved to obtain a selenium precursor solution.
[0023] Furthermore, the molar concentration of the zinc precursor solution is 0.5-50mmol / ml, and the synthesis method is: in an argon environment, the zinc source and the organic solvent are mixed, stirred, and heated to 250-280°C to completely dissolve the solid to obtain a zinc precursor solution.
[0024] Furthermore, the molar concentration of the cadmium precursor solution is 0.5-50mmol / ml, and the synthesis method is: in an argon environment, the cadmium source and the organic solvent are mixed, stirred, and heated to 250-280°C to completely dissolve the solid to obtain a cadmium precursor solution.
[0025] Furthermore, the anion source is a sulfur source or a selenium source; and the cation source is a zinc source or a cadmium source.
[0026] Furthermore, the sulfur source is one of sulfur powder, dodecyl mercaptan and octyl mercaptan.
[0027] Furthermore, the selenium source is selenium powder.
[0028] Furthermore, the zinc source is one of zinc oxide, zinc acetate and zinc stearate.
[0029] Furthermore, the cadmium source is one of cadmium oxide, cadmium acetate and cadmium stearate.
[0030] Furthermore, the organic solvent includes a coordinating solvent and / or a non-coordinating solvent. The coordinating solvent is a saturated or unsaturated fatty acid with a carbon number of ≥5 and / or a saturated or unsaturated amine compound with a carbon number of ≥6, preferably oleic acid. The non-coordinating solvent is one or a combination of any two or more of an alkane, olefin, ether or aromatic compound with a carbon number of ≥10 and ≤22, preferably octadecene.
[0031] Furthermore, the long-chain alkyl phosphine is tributyl phosphine or trioctyl phosphine.
[0032] Further, step 2) is specifically as follows: in an argon environment, the cation source, the coordinating solvent and the non-coordinating solvent are mixed, the temperature is raised to 280-350°C, the anion precursor solution is quickly injected, the reaction is carried out for 30s-15min, the liquid is cooled to room temperature, and then centrifuged and dried to obtain quantum dot cores.
[0033] Furthermore, the anion precursor is one or both of a sulfur precursor and a selenium precursor; and the cation source is one or both of a zinc source and a cadmium source.
[0034] Furthermore, the molar ratio of the cation source to the coordinating solvent is 1:2-1:6; and the volume ratio of the coordinating solvent to the non-coordinating solvent is 2:1-1:20.
[0035] Furthermore, the molar ratio of the cation source to the anion precursor solution is 1:30-5:1.
[0036] Furthermore, the injection time is 1-10s.
[0037] Further, step 3) is specifically as follows: dissolving the quantum dot core with a non-polar organic solvent, adding a cationic precursor solution, a ZnX solution and a non-coordinating solvent to the resulting solution, heating to 290-310° C. under nitrogen protection, and keeping warm for 0.5-1.5 hours to obtain a repaired quantum dot core.
[0038] Furthermore, the molar ratio of the quantum dot core solution, the cationic precursor solution and the ZnX solution is 1:2:1-1:20:5.
[0039] Furthermore, the non-polar organic solvent is one of hexane, octane, toluene and chloroform.
[0040] In the present invention, the ZnX solution is prepared by the following method: in an argon environment, ZnX is mixed with an organic solvent, the temperature is raised to 280° C. and kept for 20 minutes, and the temperature is lowered to 100° C. and kept for standby use.
[0041] In the present invention, the molar concentration of the ZnX solution is 2-10 mmol / ml.
[0042] Furthermore, the molar ratio of ZnX to the organic solvent is 1:2-1:5.
[0043] Further, step 4) is specifically as follows: add the anion precursor solution to the quantum dot core solution repaired in step 3, keep warm for 0.5-1.5 hours, cool to room temperature, centrifuge the resulting liquid, and dry it to obtain the quantum dots with high ultraviolet absorption.
[0044] Furthermore, in step 4), the molar ratio of the anion precursor solution to the cationic precursor solution in step 3) is 5:1-1:5.
[0045] The dropping speed of the dropping is 0.8-1.2 ml / h.
[0046] The present invention also provides a quantum dot, which is prepared by the above preparation method.
[0047] The quantum dots provided by the present invention broaden the range of ultraviolet absorption, improve the ability of ultraviolet absorption, and simultaneously improve the efficiency of the quantum dots.
[0048] The present invention also provides the application of the quantum dots in the preparation of photovoltaic modules.
[0049] The use of the quantum dots of the present invention to prepare photovoltaic modules can absorb more ultraviolet light and convert it into visible light that can be used by the photovoltaic modules, which can not only improve the photoelectric conversion efficiency of the modules, but also increase the service life of the modules.
[0050] Compared with the prior art, the present invention has the following advantages:
[0051] The method of the present invention is used to prepare quantum dots, which broadens the range of ultraviolet absorption, improves the ability of ultraviolet absorption, and improves the efficiency of quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The UV-visible absorption spectra of quantum dots of Example 1 and Comparative Example 1;
[0053] Figure 2 The fluorescence intensity spectra of quantum dots of Example 1 and Comparative Example 1 are shown; DETAILED DESCRIPTION
[0054] The following are specific embodiments of the present invention, and the embodiments are intended to further describe the present invention rather than to limit the present invention.
[0055] Example 1. Preparation of CdZnS-ZnCl2 / ZnS
[0056] 1) Prepare the precursor solution required for the reaction
[0057] ① Preparation of the first sulfur precursor S-ODE solution: Under argon environment, 5 mmol of S was added to 10 ml of octadecene (ODE) solution, and the temperature was raised to 120°C and kept warm for 60 min until the solid was completely dissolved to obtain a S-ODE solution with a concentration of 0.5 mmol / ml, which was kept warm at 100°C for later use.
[0058] ② Preparation of the second sulfur precursor TOPS solution: Under argon environment, 5 mmol of S was added to 10 ml of trioctylphosphine (TOP) solution and stirred until the solid was completely dissolved to obtain a TOPS solution with a concentration of 0.5 mmol / ml for standby use.
[0059] ③ Preparation of zinc precursor solution: Under argon environment, add 20 mmol zinc acetate, 20 ml oleic acid and 20 ml octadecene (ODE) into a four-necked bottle, stir and heat to 280 °C and keep warm for 20 min until the solution is clear to obtain zinc precursor solution, cool to 100 °C and keep warm for later use.
[0060] 2) Preparation of quantum dot cores
[0061] 1mmol cadmium oxide, 10mmol zinc acetate, and 10ml oleic acid were added to a four-necked flask, heated to 120°C under nitrogen protection for 1h, then 20ml octadecene was added, the temperature was continued to rise to 300°C, and the S-ODE solution (3ml) was quickly injected for 12min, and cooled to room temperature. The liquid was centrifuged three times and dried to obtain quantum dot cores.
[0062] 3) Repair the quantum dot core using ZnCl2 solution
[0063] Preparation of ZnCl2 solution: Under argon environment, add 10mmol ZnCl2, 20ml oleic acid and 20ml octadecene (ODE) into a four-necked bottle, stir and heat to 280℃ and keep warm for 20min until the solution is clear, then cool to 100℃ and keep warm for later use.
[0064] The quantum dot core was dissolved in toluene into a solution with a concentration of 0.5 mmol / ml, 5 mmol zinc precursor solution, 15 mmol ZnCl2 solution and 50 ml octadecene were added to the resulting solution, and the temperature was raised to 300°C under argon protection and kept for 1 hour to obtain the repaired quantum dot core.
[0065] 4) Encapsulate the repaired quantum dot core with a precursor solution
[0066] 10 ml of TOPS solution was added to the repaired quantum dot core solution at a rate of 1 ml / h, and after the addition was completed, the solution was kept warm for 1 hour and cooled to room temperature. The liquid was centrifuged three times and dried to obtain the CdZnS-ZnCl2 / ZnS quantum dots with high ultraviolet absorption.
[0067] Example 2. Preparation of CdZnSeS-ZnBr2 / ZnS
[0068] 1) Prepare the precursor solution required for the reaction
[0069] ① Preparation of sulfur precursor TOPS solution: Under argon environment, add 5 mmol of sulfur powder to 10 ml of trioctylphosphine (TOP) solution and stir until the solid is completely dissolved to obtain a TOPS solution with a concentration of 0.5 mmol / ml for standby use.
[0070] ② Preparation of selenium precursor TOPSe: Under argon environment, add 2 mmol of selenium powder into 10 ml of trioctylphosphine (TOP) solution and stir until the solid is completely dissolved to obtain a TOPSe solution with a concentration of 0.2 mmol / ml for standby use.
[0071] ③ Preparation of zinc precursor solution: Under argon environment, add 20mmol zinc acetate, 20ml oleic acid and 20ml octadecene (ODE) into a four-necked flask, stir and heat to 280℃ and keep warm for 20min until the solution becomes clear to obtain zinc precursor solution, cool to 100℃ and keep warm for later use.
[0072] 2) Preparation of quantum dot cores
[0073] 1mmol cadmium oxide, 20mmol zinc oxide, and 20ml oleic acid were added to a four-necked flask, heated to 120°C under nitrogen protection gas and kept warm for 1h, then 40ml octadecene was added, the temperature was continued to rise to 310°C, TOPS solution (6ml) and TOPSe solution (10ml) were quickly injected, kept warm for 10min, and cooled to room temperature. The liquid was centrifuged three times and dried to obtain quantum dot cores.
[0074] 3) Repair the quantum dot core using ZnBr2 solution
[0075] Preparation of ZnBr2 solution: Under argon environment, add 15mmol ZnBr2, 30ml oleic acid and 30ml octadecene (ODE) into a four-necked bottle, stir and heat to 280℃ and keep warm for 20min until the solution is clear, then cool to 100℃ and keep warm for later use.
[0076] The quantum dot core was dissolved in toluene into a solution with a concentration of 0.5 mmol / ml, 10 mmol zinc precursor solution, 15 mmol ZnBr2 solution and 30 ml octadecene were added to the resulting solution, and the temperature was raised to 310°C under argon protection and kept for 1 hour to obtain the repaired quantum dot core.
[0077] 4) Encapsulate the repaired quantum dot core with a precursor solution
[0078] 16 ml of TOPS solution was added to the repaired quantum dot core solution at a rate of 0.8 ml / h, and after the addition was completed, the solution was kept warm for 1 hour and cooled to room temperature. The liquid was centrifuged three times and dried to obtain the CdZnSeS-ZnBr2 / ZnS quantum dots with high ultraviolet absorption.
[0079] Example 3. Preparation of CdZnSe-Zn(SH)2 / CdZnS
[0080] 1) Prepare the precursor solution required for the reaction
[0081] ① Preparation of selenium precursor TOPSe solution: Under argon environment, 5 mmol of selenium powder was added to 50 ml of trioctylphosphine (TOP) solution and stirred until the solid was completely dissolved to obtain a TOPSe solution with a concentration of 0.1 mmol / ml for standby use.
[0082] ② Preparation of sulfur precursor TOPS solution: Under argon environment, add 5 mmol of sulfur powder to 10 ml of trioctylphosphine (TOP) solution and stir until the solid is completely dissolved to obtain a TOPS solution with a concentration of 0.5 mmol / ml for standby use.
[0083] ③ Preparation of zinc precursor solution: Under argon environment, add 20 mmol zinc acetate, 20 ml oleic acid and 20 ml octadecene (ODE) into a four-necked bottle, stir and heat to 280 °C and keep warm for 20 min until the solution is clear to obtain zinc precursor solution, cool to 100 °C and keep warm for later use.
[0084] ④ Preparation of cadmium precursor solution: Under argon environment, add 20mmol cadmium oxide, 20ml oleic acid and 20ml octadecene (ODE) into a four-necked bottle, stir and heat to 280℃ and keep warm for 20min until the solution becomes clear to obtain cadmium precursor solution, cool to 100℃ and keep warm for later use.
[0085] 2) Preparation of quantum dot cores
[0086] 1mmol cadmium oxide, 10mmol zinc acetate, and 15ml oleic acid were added to a four-necked flask, heated to 120°C under nitrogen protection gas and kept warm for 1h, then 30ml octadecene was added, the temperature was continued to rise to 310°C, TOPSe solution (30ml) was quickly injected, kept warm for 10min, and cooled to room temperature. The liquid was centrifuged three times and dried to obtain quantum dot cores.
[0087] 3) Repairing the quantum dot core using Zn(SH)2 solution
[0088] Preparation of Zn(SH)2 solution: Under argon environment, add 10mmol Zn(SH)2, 30ml oleic acid and 30ml octadecene (ODE) into a four-necked bottle, stir and heat to 280℃ and keep warm for 20min until the solution is clear, then cool to 100℃ and keep warm for later use.
[0089] The quantum dot core was dissolved in toluene into a solution with a concentration of 0.5 mmol / ml, 20 mmol zinc precursor solution, 10 mmol cadmium precursor solution, 15 mmol Zn(SH)2 solution and 40 ml octadecene were added to the resulting solution, and the temperature was raised to 310°C under argon protection and kept warm for 1 hour to obtain the repaired quantum dot core.
[0090] 4) Encapsulate the repaired quantum dot core with a precursor solution
[0091] 16 ml of TOPS solution was added to the repaired quantum dot core solution at a rate of 0.8 ml / h. After the addition was completed, the solution was kept warm for 1 hour and cooled to room temperature. The liquid was centrifuged three times and dried to obtain the CdZnSe-Zn(SH)2 / CdZnS quantum dots with high ultraviolet absorption.
[0092] Comparative Example 1: Preparation of CdZnS / ZnS
[0093] This comparative example refers to Example 1, and the difference from Example 1 is that the ZnX solution is not used to repair the quantum dot core after centrifugation. Specifically:
[0094] 1) Prepare the precursor solution required for the reaction
[0095] ① Preparation of the first sulfur precursor S-ODE solution: Under argon environment, 5 mmol of S was added to 10 ml of octadecene (ODE) solution, and the temperature was raised to 120°C and kept warm for 60 min until the solid was completely dissolved to obtain a S-ODE solution with a concentration of 0.5 mmol / ml, which was kept warm at 100°C for later use.
[0096] ② Preparation of the second sulfur precursor TOPS solution: Under argon environment, 5 mmol of S was added to 10 ml of trioctylphosphine (TOP) solution and stirred until the solid was completely dissolved to obtain a TOPS solution with a concentration of 0.5 mmol / ml for standby use.
[0097] ③ Preparation of zinc precursor solution: Under argon environment, add 20 mmol zinc acetate, 20 ml oleic acid and 20 ml octadecene (ODE) into a four-necked bottle, stir and heat to 280 °C and keep warm for 20 min until the solution is clear to obtain zinc precursor solution, cool to 100 °C and keep warm for later use.
[0098] 2) Preparation of quantum dot cores
[0099] 1mmol cadmium oxide, 10mmol zinc acetate, and 10ml oleic acid were added to a four-necked flask, heated to 120°C under nitrogen protection for 1h, then 20ml octadecene was added, the temperature was continued to rise to 300°C, and the S-ODE solution (3ml) was quickly injected for 12min, and cooled to room temperature. The liquid was centrifuged three times and dried to obtain quantum dot cores.
[0100] 3) Encapsulation of quantum dot cores using precursor solution
[0101] The quantum dot core was dissolved in toluene to form a solution with a concentration of 0.5 mmol / ml. 5 mmol of zinc precursor solution and 50 ml of octadecene were added to the resulting solution. The temperature was raised to 300 °C under argon protection. 10 ml of TOPS solution was added dropwise at a rate of 1 ml / h. After the addition was completed, the solution was kept warm for 1 hour and cooled to room temperature. The liquid was centrifuged three times and dried to obtain CdZnS / ZnS quantum dots. Test Example 1: UV absorption and luminescence performance test
[0102] The quantum dot samples prepared in Example 1 and Comparative Example 1 were dissolved in toluene to form a solution with a concentration of 0.5 mmol / ml for optical performance testing. The test was carried out using the relative method, and the ultraviolet absorption and fluorescence intensity of the quantum dots were measured according to the national standards GB / T 37664.1-2019 and GB / T36081-2018. The results are as follows Figure 1 and Figure 2 shown.
[0103] from Figure 1 and Figure 2 It can be seen that, compared with Comparative Example 1, the quantum dots prepared by the method of the present invention have significantly enhanced absorption in the ultraviolet region and improved fluorescence intensity.
[0104] Test Example 2: Photovoltaic Module Performance Test
[0105] Take 0.3g of quantum dots, 30g of EVA particles, 0.3g of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 0.2g of triallyl isocyanurate, 0.1g of γ-(methacryloyloxy)propyltrimethoxysilane, 0.03g of bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, and 0.02g of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid n-octadecanol ester, mix them evenly, then melt-extrude and form a quantum dot adhesive film with a thickness of 0.5mm using a casting method at 140°C.
[0106] After photovoltaic glass, quantum dot adhesive film, solar cell, quantum dot adhesive film and lower photovoltaic glass are stacked in order from bottom to top on the photovoltaic glass, they are placed in a vacuum laminator. After vacuuming for 10 minutes, the temperature is raised to 120°C and laminated at a pressure of 25 MPa to obtain a photovoltaic module.
[0107] Example 1 and Comparative Example 1 were used as quantum dots added to the adhesive film to prepare the adhesive film and laminated to obtain a photovoltaic module. The module power was tested and the attenuation rate was calculated for comparison. The power test standard of the photovoltaic module was carried out in accordance with IEC61215-2:2021, and the anti-PID performance test standard was carried out in accordance with IEC61215-2:2021.
[0108] The test results are shown in Table 1.
[0109] Table 1
[0110]
[0111] It can be concluded from Table 1 that for the photovoltaic modules using Example 1 and Comparative Example 1 as light conversion factors, the initial power of Example 1 is increased by about 0.09% compared with Comparative Example 1. This is because the ultraviolet absorption capacity of the quantum dots obtained in Example 1 is higher than that of Comparative Example 1, so more ultraviolet light can be converted into visible light, thereby increasing the initial power of the module. After irradiation with UV3000KWH, the power of Example 1 can still be maintained at 97% of the initial power. On the one hand, the quantum dots have high stability, and on the other hand, the quantum dots of Example 1 enhance the absorption of ultraviolet light, reducing the impact of ultraviolet light on the module.
Claims
1. A method for preparing quantum dots with high ultraviolet absorption, characterized in that: The preparation method comprises the following steps: 1) preparing the precursor solution required for the reaction; 2) preparing quantum dot cores; 3) Repairing the quantum dot core using ZnX solution; 4) Encapsulating the repaired quantum dot core with a precursor solution to form quantum dots having a quantum dot core-ZnX repair layer-quantum dot shell structure, thereby obtaining the quantum dots with high ultraviolet absorption.
2. The preparation method according to claim 1, characterized in that: In step 1), the precursor solution includes an anion precursor solution and a cationic precursor solution; The preparation method of the anion precursor solution is as follows: under an argon environment, an anion source is added to an organic solvent or a long-chain alkyl phosphine until the solid is completely dissolved to obtain an anion precursor solution; The preparation method of the cationic precursor solution is: in an argon environment, a cationic source is mixed with an organic solvent until the solid is completely dissolved to obtain a cationic precursor.
3. The preparation method according to claim 1, characterized in that: Step 2) is specifically as follows: in an argon environment, the cation source, the coordinating solvent and the non-coordinating solvent are mixed, the temperature is raised to 280-350°C, the anion precursor solution is quickly injected, the reaction is carried out for 30s-15min, the liquid is cooled to room temperature, and then centrifuged and dried to obtain quantum dot cores.
4. The preparation method according to claim 3, characterized in that: The molar ratio of the cation source to the coordination solvent is 1:2-1:6; the volume ratio of the coordination solvent to the non-coordinating solvent is 2:1-1:20; and the molar ratio of the cation source to the anion precursor solution is 1:30-5:
1.
5. The preparation method according to claim 3 or 4, characterized in that: Step 3) is specifically as follows: dissolving the quantum dot core with a non-polar organic solvent, adding a cationic precursor solution, a ZnX solution and a non-coordinating solvent to the resulting solution, heating to 290-310° C. under nitrogen protection, and keeping the temperature for 0.5-1.5 h to obtain a repaired quantum dot core.
6. The preparation method according to claim 5, characterized in that: The molar ratio of the quantum dot core solution, the cationic precursor solution and the ZnX solution is 1:2:1-1:20:
5.
7. The preparation method according to claim 1, characterized in that: Step 4) is specifically as follows: add the anion precursor solution to the repaired quantum dot core solution, keep the solution warm for 0.5-1.5h, cool the solution to room temperature, centrifuge the solution, and dry the solution to obtain the quantum dots with high ultraviolet absorption.
8. The preparation method according to claim 7, characterized in that: In step 4), the molar ratio of the anion precursor solution to the cationic precursor solution in step 3) is 5:1-1:
5.
9. Quantum dots with high ultraviolet absorption obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the quantum dots according to claim 9 in preparing photovoltaic modules.
Citation Information
Patent Citations
CdSe / CdS / ZnS quantum dot preparation method
CN105462575A
Preparing method for CdSe / CdZnSeS / ZnS core-shell quantum dots
CN107090291A
Synthesis method of ZnS / CdZnS / ZnS blue light quantum dot
CN110041907A
Preparation of CdSeZnS / ZnS / ZnS core / shell / core quantum dot
CN110129055A
Core-shell InP / ZnSe / ZnS quantum dot and preparation method thereof
CN112608752A